Positive parents and negative peers: assessing the nature and order of caregiver and friend effects in predicting early delinquency - Walters, Glenn D. (Youth violence and juvenile justice, 2020)
The purpose of this study was to evaluate the nature and direction of the relationship between parenting and peer effects in predicting early delinquency. The parenting-peer relationship was evaluated in 1,734 (811 male, 923 female) early adolescent members (mean age = 12.10 years) of the Gang Resistance Education and Training (GREAT) study. A seven-equation path analysis was performed across three waves of data. The statistical significance of 16 indirect effects was evaluated using the Monte Carlo Method for Assessing Mediation. Two of the three pathways predicted to be significant were, in fact, significant (i.e., parental support to gang affiliation to participant delinquency; parental support to peer delinquency to participant delinquency), and all 13 pathways projected to be nonsignificant were, in fact, nonsignificant. Consistent with the research hypothesis for this study, prior parental support acted as a buffer against the delinquency-promoting effects of negative peer associations in early adolescent children.